Upregulation of Ugt1a genes in placentas and fetal livers in a murine model of assisted reproduction - Collier, Abby C. (2011)
Genes from Ugt1a family in placenta and fetal liver are responsible for hormone, nutrient and chemical balance during pregnancy. Assisted reproduction technologies (ART) i.e. intracytoplasmic sperm injection (ICSI) and in vitro fertilization (IVF) alter steroid homeostasis in pregnancy through increased glucuronidation. Here we show that ART (particularly ICSI) upregulates Ugt1a1, 1a2, 1a6 and 1a9 expression in murine placentas and fetal livers with higher mRNA related to lower progesterone (1a1) and cholesterol (1a2, 1a6) in placentas. Greater steroid clearance in ART through transcriptional upregulation of Ugt1a in the placental-fetal unit may decrease the availability of essential molecules, mediating negative reproductive outcomes.